Where's Wally: the influence of visual salience on referring expression generation - Clarke, Alasdair D.; Elsner, Micha; Rohde, Hannah (Frontiers in Psychology, 2013)
Referring expression generation (REG) presents the converse problem to visual search: Given a scene and a specified target, how does one generate a description which would allow somebody else to quickly and accurately locate the target? Previous work in psycholinguistics and natural language processing that has addressed this question identifies only a limited role for vision in this task. That previous work, which relies largely on simple scenes, tends to treat vision as a pre-process for extracting feature categories that are relevant to disambiguation. However, the visual search literature suggests that some descriptions are better than others at enabling listeners to search efficiently within complex stimuli. This paper presents the results of a study testing whether speakers are sensitive to visual features that allow them to compose such `good' descriptions. Our results show that visual properties (salience, clutter, area, and distance) influence REG for targets embedded in images from the *Where's Wally?* books, which are an order of magnitude more complex than traditional stimuli. Referring expressions for large salient targets are shorter than those for smaller and less salient targets, and targets within highly cluttered scenes are described using more words. We also find that speakers are more likely to mention non-target landmarks that are large, salient, and in close proximity to the target. These findings identfy a key role for visual salience in language production decisions and highlight the importance of scene complexity for REG.